2002
DOI: 10.2169/internalmedicine.41.133
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Expanding Lung Abscess Caused by Legionella pneumophila in Immunocompromised Patients: A Report of Two Cases.

Abstract: Wedescribe two cases of lung abscess caused by Legionella pneumophila in immunocompromisedpatients.The first case had been treated initially with 60 mg prednisolone for ulcerative colitis, and L. pneumophilaserogroup 1 was isolated from sputum samples after cavitation of the lung lesion. The second case was diagnosed as plasma cell lymphomaat post-mortem examination. L. pneumophila serogroup 5 was isolated from the contents of lung abscess, together with Enterococcus faecium and Prevotella intermedia in the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…120 Risk factors for Legionella spp. 121,123 In vitro data from mice demonstrating that TNF-a is critical for clearing macrophage infection with Legionella further supports the hypothesis of an increased risk of L. pneumophila infection among patients treated with anti-TNF-a antagonists. 121,122 Besides corticosteroids, it has been shown that combined immunosuppression or use of anti-TNF-a antagonists in patients with IBD and rheumatoid arthritis has been associated with an increased risk of Legionella pneumonia.…”
Section: Legionellosismentioning
confidence: 71%
“…120 Risk factors for Legionella spp. 121,123 In vitro data from mice demonstrating that TNF-a is critical for clearing macrophage infection with Legionella further supports the hypothesis of an increased risk of L. pneumophila infection among patients treated with anti-TNF-a antagonists. 121,122 Besides corticosteroids, it has been shown that combined immunosuppression or use of anti-TNF-a antagonists in patients with IBD and rheumatoid arthritis has been associated with an increased risk of Legionella pneumonia.…”
Section: Legionellosismentioning
confidence: 71%
“…Human disease occurs when aerosolized L. pneumophila is inhaled from man-made or natural freshwater reservoirs harboring the bacteria. L. pneumophila poses a significant worldwide public health problem, particularly for individuals with compromised immune systems (19,38,40). Eradication of the pathogen from freshwater, industrial settings has proven difficult, since L. pneumophila thrives in environments that exclude antibacterial agents, such as biofilms and the intracellular compartments of protozoa (8,46,47).…”
mentioning
confidence: 99%
“…To our knowledge, this is the first report on E. faecium causing pulmonary infection (abscesses) as a single pathogen since a mixture of pulmonary pathogens including E. faecium has been documented so far [3]. Undoubtedly, both profound immunosupression with antithymocyte globulin and urinary leak contributed to this condition in our patient.…”
mentioning
confidence: 66%